Monitoring of Separate Pathogenetically Significant Biochemical Markers in Lacrimal Fluid, Ophthalmological Parameters with Combined Pathology of Diabetic Retinopathy and Age-Related Macular Degeneration on the Background Angioprotective and Antioxidant Therapy - I. V. Vorobyeva (Oftalʹmologiâ, 2018)
Object: Optimization of treatment in early stages of combined fundus pathology diabetic retinopathy (DR without DME) and dry type of age-related macular degeneration (AMD AREDS I, II, III).Patients and methods: 120 people (150 eyes). Study group 1 (SG1) — control 60 people. (60 eyes); study group 2 (SG2) — 30  people. (30 eyes) — DRI without DME and AMD AREDS I, II, III)  treatment: 1 year with angioprotective calcium dobezilate (Doxi- Hem®) dose of 500 mg 3 after 6 months, 500 mg once a day for 6  months and at the same time 1 year antioxidant agent (Retinorm) 1  capsule 3 times a day; study group 3 group (SG3) 30 people. (30  eyes) — with DRO and dry type of AMD (AREDS I, II, III) 1 year  Retinorm 1 capsule 3 times a day; study group 4 (SG4) with DRI  without DME — 30 people. (30 eyes) 1 year Doxi-Hem®. Monitoring: monthly standard ophthalmologic examination, control of diabetes  mellitus (HbA1C) compensation, VEGF-A vascular endothelial growth  factor in tear.Results. Visual acuity increased on the background of treatment in  all three groups (IG2,3,4): in SG2 from 0.72 ± 0.02 to 0.87 ± 0.02,  p < 0.05; the thickness of the retina decreased from 290.2 ± 2.1 to  268.85 ± 2.2 μm, p < 0.05, the photosensitivity increased from 21.0 ± 0.2 to 25.1 ± 0.2 dB p < 0.05; in the tear VEGF-A to 415.4 ± 4.6  pg/ml, p < 0.05. In SG3, visual acuity increased from 0.74 ± 0.02 to  0.88 ± 0.02, p < 0.05; the thickness of the retina decreased from 287.7 ± 2.0 to 272.8 ± 2.2 μm (р < 0.05); increased photosensitivity from 21.3 ± 0.2 to 24.5 ± 0.2 dB, p < 0.05; in the  VEGF-A slip to 416.6 ± 5.0 pg/ml, p > 0.05. In IG4 visual acuity  increased from 0.70 ± 0.02 to 0.78 ± 0.02, p < 0.05; the thickness  of the retina decreased from 288.1 ± 4.4 to 280.1 ± 2.4 μm, р <  0.05; the photosensitivity increased from 21.2 ± 0.2 to 23.2 ± 0.2 dB; VEGF-A up to 415.9 ± 3.8 pg/ml, p > 0.05.Conclusion. Combined therapy of angioprotective (Doxi-Hem®) and antioxidant therapy (Retinorm) with timely appointment at early dry  stages of combined pathology (DR and AMD) will allow to stabilize, delay the development of severe forms of the disease.